Rock engineering design - Feng, Xia-Ting (CRC Press/Balkema, 2011)
"Given the recent advances in site investigation techniques, computing, access to information and monitoring, plus the current emphasis on safety, accountability and sustainability, the intention of this book is to introduce an up-to-date methodology for the design of all types of rock engineering projects, whether surface or underground. Guidance is provided on the nature of the modeling to support design